2018
DOI: 10.1016/j.sjopt.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conjunctival autograft and conjunctival transposition flap techniques in primary pterygium surgery

Abstract: Both conjunctival transpositional flap and conjunctival autograft techniques have same results in terms of pterygium recurrence and surgery complications in the treatment of primary pterygium. Surgery time in conjunctival transpositional flap technique is significantly shorter. Conjunctival transpositional flap technique may be a good alternative method for primary pterygıum surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
(14 reference statements)
1
14
1
1
Order By: Relevance
“…Syam et al reported a recurrence rate of 3.3% in their study, similar to the results obtained in a case series conducted by Bilge, 40 while Koranyi et al, Fernandes et al, Ma et al, and Al Fayez reported 13.5%, 12.2%, 5.4%, and 8.3% recurrence rates, respectively. 31 , 41 43 However, much higher recurrence rates have been reported (ranging from 31.3% to 33.3%), in case of recurrent pterygium excision.…”
Section: Surgical Treatmentsupporting
confidence: 83%
See 3 more Smart Citations
“…Syam et al reported a recurrence rate of 3.3% in their study, similar to the results obtained in a case series conducted by Bilge, 40 while Koranyi et al, Fernandes et al, Ma et al, and Al Fayez reported 13.5%, 12.2%, 5.4%, and 8.3% recurrence rates, respectively. 31 , 41 43 However, much higher recurrence rates have been reported (ranging from 31.3% to 33.3%), in case of recurrent pterygium excision.…”
Section: Surgical Treatmentsupporting
confidence: 83%
“… 31 , 41 43 However, much higher recurrence rates have been reported (ranging from 31.3% to 33.3%), in case of recurrent pterygium excision. 40 A novel technical variant named “pterygium extended removal followed by extended conjunctival transplantation” (P.E.R.F.E.C.T.) was conducted in Australia, with reports of patients’ follow-up longer than 1 year and a recurrence rate of 1.6%.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Age, hereditary factors, sunlight, chronic inflammation, microtrauma, and heat are possible contributing factors [2]. Due to the lack of effective therapeutic drugs, pterygium excision, combined with autologous conjunctival grafting, has been suggested as the best treatment for this disorder [3].…”
Section: Introductionmentioning
confidence: 99%